2010
DOI: 10.3390/molecules15107188
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Carbon-Based Solid Acid Catalyst by Sulfonating Activated Carbon in a Chemical Reduction Process

Abstract: Sulfonated (SO3H-bearing) activated carbon (AC-SO3H) was synthesized by an aryl diazonium salt reduction process. The obtained material had a SO3H density of 0.64 mmol·g−1 and a specific surface area of 602 m2·g−1. The catalytic properties of AC-SO3H were compared with that of two commercial solid acid catalysts, Nafion NR50 and Amberlyst-15. In a 10-h esterification reaction of acetic acid with ethanol, the acid conversion with AC-SO3H (78%) was lower than that of Amberlyst-15 (86%), which could be attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
160
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(175 citation statements)
references
References 20 publications
13
160
0
2
Order By: Relevance
“…Compared to previous reports [25,[42][43][44][45][46][52][53][54][55][56][57][58], this study also demonstrated that the surface area of the catalytic systems can be manipulated by the synthetic methodology. As can be observed from the obtained data, the acidic SiO 2 catalyst varies in the surface area in comparison to the one prepared from TEOS and displays more activity towards the Pechmann reaction.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…Compared to previous reports [25,[42][43][44][45][46][52][53][54][55][56][57][58], this study also demonstrated that the surface area of the catalytic systems can be manipulated by the synthetic methodology. As can be observed from the obtained data, the acidic SiO 2 catalyst varies in the surface area in comparison to the one prepared from TEOS and displays more activity towards the Pechmann reaction.…”
Section: Methodsmentioning
confidence: 80%
“…Even though there are several studies addressing the catalytic performance of a variety of heterogeneous solid catalysts in producing coumarin compounds via Pechmann condensation, most of these methodologies suffer from some drawbacks such as long reaction time, swelling tendency, low surface area, stability of the catalysts and their costs [51][52][53][54][55][56][57]. In order to overcome some of these obstacles and as a continuation to our research in developing a new and efficient catalytic protocol for the effective synthesis of coumarins, this report elucidates the synthesis of three new catalytic systems of sulphated and phosphated nanoparticle of silica, titania and silica prepared from TEOS catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…area of 602m 2 /g gave 78% while the Amberlyst-15 with 4.60 mmol/g SO 3 H groups gave 86% yield. The yield was higher for the longer chain decanoic acid but the leaching of the activated carbon catalyst was a problem [9].…”
Section: I-1biobased Catalyst From Glucose and Sucrosementioning
confidence: 99%
“…Better catalytic activity for making biodiesel type molecules, was found to be due to the large surface area and mesoporous structure of the activated carbon [9]. Sulfonation of FDU-15, a mesoporous polymer, produced a catalyst which affected 99% conversion in esterification of palmitic acid using methanol at 343k temperature.…”
Section: I-5other Methods Of Making Sulfonated (Biobased) Catalystsmentioning
confidence: 99%
See 1 more Smart Citation